Effects of flame‐retardant additives on the manufacturing, mechanical, and fire properties of basalt fiber‐reinforced polybenzoxazine. Issue 2 (16th December 2020) - Wolter, Nick; Carrillo Beber, Vinicius; Haubold, Thorben; Sandinge, Anna; Blomqvist, Per; Goethals, Frederik; Van Hove, Marc; Jubete, Elena; Mayer, Bernd; Koschek, Katharina
Abstract: Basalt fiber‐reinforced polybenzoxazines (BFRP) were manufactured through vacuum infusion using resorcinol bis (diphenyl phosphate) and poly‐(m‐phenylene methylphosphonate) together with bisphenol‐F and aniline based benzoxazine. Different types and loadings of flame‐retardant additives showed to have catalysis or dilution effects in viscosity measurements. BFRPs show well‐penetrated fibers and near‐zero porosity. Additive addition did not influence tensile properties, while apparent interlaminar shear strength decreased indicating a lower adhesion between fiber and matrix. BFRP's heat and smoke release properties increased, though time to ignition increased and flammability behavior improved by decreasing delamination yielding oxygen indices in between 72 and 91%. Abstract : Flame retardant additives showed catalytic or dilution effects on benzoxazines and retained composite integrity, which improves flammability properties during combustion of basalt fiber reinforced polybenzoxazines.